Efektivitas Pemberian Fermentasi Beras Merah (Oryza sativa) dan Beras Hitam (Oryza sativa L. indica) terhadap Tekanan Darah Ibu Hamil Preeklamsia - Khoerunnisa, Asma Alfiah; Novitasari, Dhini Wahyuni; Billah, Muhammad Muayyad (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2026)
Background: Preeclampsia is a hypertensive disorder of pregnancy for approximately 75% of direct maternal deaths. Early detection and promoting healthier nutritional alternatives are strategies to mitigate its risks. Fermented red rice and black rice may serve as dietary interventions due to bioactive compounds such as lovastatin that may support maternal health in preeclampsia. Objective: To compare and analyze the effect of fermented red rice and black rice on the blood pressure of pregnant women with preeclampsia. A true experimental research design with randomized pretest-posttest control-group design. Methods: The study conducted from August-September 2025, involved 60 pregnant women with preeclampsia in the working area of Cikalongwetan Regional Hospital. Participants were randomly assigned to three groups, a fermented red rice, a fermented black rice, and a control receiving mineral water. Each group received 5mL of their intervention twice daily for four weeks. Data were analyzed using Paired Sample t-test and One Way ANOVA. Results: The results after four-week intervention showed significant differences in blood pressure reduction among the groups. Fermented red rice showed the most decrease, with mean reduction of 22.5 mmHg in systolic blood pressure and 12.5 mmHg in diastolic blood pressure. Fermented black rice also showed reduction, averaging 14.5 mmHg (systolic) and 11.5 mmHg (diastolic). The One-Way ANOVA confirmed a statistically significant difference, the mean post intervention systolic (p=0.025) and diastolic (p=0.007) blood pressure among the groups. Conclusion: The reduction in blood pressure was greater fermented red rice group compared to fermented black rice group.non- pharmacological pain management during labor.